An Observational Prospective Study on Effectiveness of Homoeopathic Management in Food Allergy – A Symptomatological Approach (Homoeopathy for All, 2024)
Background: A food allergy is  an unfavorable reaction with an  immunological basis that develops  after exposure to a particular food on  a regular basis. When the immune  system is unable to develop or  maintain oral tolerance to specific  dietary proteins, food allergies  develop. Objectives: To study the  effectiveness of homoeopathic  management in food allergies.  Methods: An Observational  Prospective Study which is  conducted at Alva’s Homoeopathic  medical college and Hospital,  Mangalore during the year 2022- 2023. 30 patients were selected  based on purposive sampling  based on inclusion and exclusion  criteria. Erlangen symptom score  was taken as assessment scale  in which all symptoms of the  patients were collected before and  after the treatment. Dr. J.T. Kent's  repertorization was used to calculate  totality. The improvement following  therapy was evaluated using a paired  t test based on the assessment scale. Results: All sorts of food allergies  can be treated safely, gently, and  effectively with homoeopathy's  symptomatological approach. After  treatment, this study's use of the  Erlangen symptom score revealed a  considerable change. After receiving  symptomatic homoeopathic  treatment, the patient improved. Conclusion: It is determined that the  homoeopathic symptomatological  method is highly efficient in treating  food allergies.
Keywords: Erlangen symptom score; idiosycrasies